Stakeholders Collaboration to Stimulate the Economic Empowerment for Salt Farmers in Pamekasan Regency - Rendra Eko Wismanu; Yudha Prakasa; Lestari Eko Wahyudi; Durratun Nashihah (Jurnal Sosial Ekonomi Kelautan dan Perikanan, 2023)
Previous studies about the dynamics of salt farming in Indonesia have shown several problems. One of the main problems is related to the management context of salt farming. An attempt to enhance salt farming management is to increase salt farmers empowerment. One of the policies declared by the government to overcome this problem is People’s Salt Business Program/ Program Usaha Garam Rakyat (PUGAR). This study aims to: (1) describe, explain and analyze the condition of the salt commodity supply chain in Pamekasan Regency, and (2) describe and explain a model of community empowerment of salt farmers in Pamekasan Regency with a value chains analysis approach, so that with this community empowerment model salt farmers in Pamekasan Regency can optimize positive impacts and minimize the negative impacts of salt business implementation in the regions aforementioned.This research uses qualitative research with a value chains analysis approach. Value chain analysis is the process by which a company identifies key activities and aids that add value to a product, then analyzes them to reduce costs or increase differentiation. The location of the study was conducted in Pamekasan Regency.The results of the research through value chain analysis show a diagram model of community empowerment of salt farmers in Pamekasan Regency, namely through the PUGAR program it has been running well in increasing the production and quality of salt commodities in Pamekasan Regency. Production activities up to salt distribution cannot be separated from the role of 3 stakeholders, including: government, private sector, and community. This study emphasizes the impact of stakeholder collaboration in community empowerment. The result of the research is expected could be used as a reference by stakeholders in formulating policies for the increase of farmers welfare.